2022
DOI: 10.1111/hel.12944
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori‐positive chronic atrophic gastritis and cellular senescence

Abstract: Background Chronic atrophic gastritis (CAG) is a pathological stage in the Correa’s cascade, whereby Helicobacter pylori (H. pylori) infection is the primary cause. Cellular senescence is an inducing factor for cancer occurrence and cellular senescence is an obvious phenomenon in gastric mucosal tissues of H. pylori‐positive CAG patients. Methods In this review, we collated the information on cellular senescence and H. pylori‐positive CAG. Results At present, only a few studies have observed the effect of cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 118 publications
0
9
0
Order By: Relevance
“…For instance, numerous studies have indicated that ROS production is considerably elevated in cagA‐positive infected gastric ulcer patients or mice compared to those infected with cagA‐negative strains 27–29 . Additionally, long‐term exposure to VacA has been shown to increase p62 and ROS levels, leading to a diminished autophagic response in host cells and facilitating an inflammatory microenvironment 30–32 . Meanwhile, Mai et al 33 demonstrated both H. pylori and lipopolysaccharide, an endotoxin derived from the outer membrane of H. pylori , accelerate the secretion of O 2 ˙ − in THP‐1 cells.…”
Section: Oxidative Stress Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, numerous studies have indicated that ROS production is considerably elevated in cagA‐positive infected gastric ulcer patients or mice compared to those infected with cagA‐negative strains 27–29 . Additionally, long‐term exposure to VacA has been shown to increase p62 and ROS levels, leading to a diminished autophagic response in host cells and facilitating an inflammatory microenvironment 30–32 . Meanwhile, Mai et al 33 demonstrated both H. pylori and lipopolysaccharide, an endotoxin derived from the outer membrane of H. pylori , accelerate the secretion of O 2 ˙ − in THP‐1 cells.…”
Section: Oxidative Stress Generationmentioning
confidence: 99%
“…[27][28][29] Additionally, long-term exposure to VacA has been shown to increase p62 and ROS levels, leading to a diminished autophagic response in host cells and facilitating an inflammatory microenvironment. [30][31][32] Meanwhile, Mai et al 33 demonstrated both H. pylori and lipopolysaccharide, an endotoxin derived from the outer membrane of H. pylori, accelerate the secretion of O 2 ˙− in THP-1 cells. Moreover, H. pylori-derived outer membrane vesicles (OMVs) containing CagA and lipopolysaccharide have been found to increase ROS levels and activate NF-κB.…”
Section: Redox Biology Of Inflammatory Cellsmentioning
confidence: 99%
“…1,2 As the most important risk factor for gastric cancer development, H. pylori infection causes mucosa-associated lymphoid tissue lymphoma, peptic ulcer disease, gastroduodenal disorders, and most common chronic gastritis, which is able to progress to chronic atrophic gastritis, dysplasia, and even gastric cancer according to the Correa cascade model. [2][3][4][5] Successful mucosal colonization on the gastric epithelium by H. pylori depends on unique bacterial properties, including bacterium spiral structure, flagellar motility, urease activity, adhesins, epithelial damage via cytotoxin-associated gene A (CagA), and vacuolar cytotoxin A (VacA), etc. [6][7][8][9] In addition, structural variations, including of flagellins and lipopolysaccharides (LPS), as well as immunosuppressive response induced by CagA, VacA, and γ-glutamyl-transpeptidase (CGT), contribute to immune escape of bacterium, thus supporting persistent gastric colonization and chronic inflammation by H. pylori.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] In addition, structural variations, including of flagellins and lipopolysaccharides (LPS), as well as immunosuppressive response induced by CagA, VacA, and γ-glutamyl-transpeptidase (CGT), contribute to immune escape of bacterium, thus supporting persistent gastric colonization and chronic inflammation by H. pylori. 4,10 The inflammasome was first proposed by Tschopp and his colleagues in 2002, who defined it as a caspase-activating complex containing caspase-1, caspase-5, Pycard, and NALP1. 11 When host cell is stimulated by pathogenic microorganisms or danger signals from itself, innate immune system will be activated to recognize these pathogen-associated molecular patterns (PAMPs) or damageassociated molecular patterns (DAMPs) through pattern recognition receptors (PRRs), thus initiating the assembly of inflammasome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation